2024
DOI: 10.5187/jast.2023.e52
|View full text |Cite
|
Sign up to set email alerts
|

The effects of synbiotics-glyconutrients on growth performance, nutrient digestibility, gas emission, meat quality, and fatty acid profile of finishing pigs

Abstract: Glyconutrients help in the body’s cell communication. Glyconutrients and synbiotics are promising options for improving immune function. Therefore, we hypothesized that combining synbiotics and glyconutrients will enhance pig nutrient utilization. 150 pigs (Landrace × Yorkshire × Duroc), initially weighing 58.85 ± 3.30 kg of live body weight (BW) were utilized to determine the effects of synbiotics-glyconutrients (SGN) on the pigs’ performance, feed efficiency, gas emission, pork traits, and composition of fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…A higher NSP level diet was advantageous to satisfy an ideal enzyme-substrate concentration for optimal enzymatic activity. In addition, the fraction of water-soluble NSP in the diet can function as a source of beneficial fermentable substrates for gut microbiota through selective fermentation, which promote the integrity of the intestinal lining, improving the digestibility of nutrient and energy, and reducing the ability of pathogenic bacteria to proliferate therefore improving the growth performance of birds [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…A higher NSP level diet was advantageous to satisfy an ideal enzyme-substrate concentration for optimal enzymatic activity. In addition, the fraction of water-soluble NSP in the diet can function as a source of beneficial fermentable substrates for gut microbiota through selective fermentation, which promote the integrity of the intestinal lining, improving the digestibility of nutrient and energy, and reducing the ability of pathogenic bacteria to proliferate therefore improving the growth performance of birds [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this study, Chlebicz-Wójcik et al [ 31 ] reported that symbiotic additives contribute to better weight gain in weaning-finishing pigs. On the other hand, Munezero et al [ 32 ] stated that the inclusion of 0.5% SB-GLN to the finishing pig diet revealed better growth performance. Awad et al [ 17 ] reported the dietary inclusion of synbiotics at the concentration of 1 g/kg showed improved body weight gain (BWG) and feed conversion ratio (FCR) in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Adding certain substrates to the diet of animals can also stimulate the development of commensal microflora. Synbiotics are a successful combination of drugs with probiotic and prebiotic effect (Duarte et al, 2020;Munezero et al, 2023). They not only positively affect the animal productivity, but also influence product quality (Saracila et al, 2021).…”
Section: Discussionmentioning
confidence: 99%